P211 Comparing standing and stepping activity in people with rheumatoid arthritis with and without foot and ankle pain. (23rd April 2022) - Quinn, Karen; Murphy, Grainne; Larkin, Louise; Leary, Helen O'
Abstract: Background/Aims: Foot and ankle pain is common in people with RA and is reported to influence physical activity levels. However there is limited objective data exploring differences in physical activity behaviours in RA in those with and without foot/ankle pain. This cross-sectional study aimed to examine the differences in objectively measured step count, cadence and standing time in people with RA reporting foot/ankle pain compared to those with no foot/ankle symptoms. Methods: Adults with RA recruited from a rheumatology outpatient department wore an ActivPAL4 accelerometer over a 7-day period. A step cadence of > 100 steps per minute was estimated to correspond to moderate physical activity. Assessments of pain intensity, location of painful joints and disease activity (Clinical Disease Activity Index-CDAI) were conducted. Cadence characteristics, total step count and standing time between groups with and without foot/ankle pain were compared using independent sample t-tests. Results: Participants (n = 72) clinical characteristics are presented in Table 1 . Current foot/ankle pain was reported by 66% (n = 47). Those with foot/ankle pain had higher disease activity as measured by CDAI and higher BMI scores. Daily standing time was less in the group with foot/ankle pain with a mean (SD) of 257 (77.7) minutes compared to 300 (95.9) minutes in those without. No significant differences in daily total step count or in any cadence characteristics were identified between groups (Table 1 ). No difference was observed in the minutes spent in moderate physical activity- foot/ankle pain group 10.6 (15.4) minutes versus no foot/ankle pain 10.6 (15.2) minutes. Conclusion: People with RA who report foot and ankle pain spend less time standing. Interestingly this study did not show differences in step count and cadence between those with and without foot and ankle pain. Participants included in this study had relatively well controlled disease. This study also only examined the presence or absence of foot pain and there was wide variation in pain levels and also daily step counts recorded. Further research exploring the relationship between activity behaviours and foot pain is warranted, particularly in populations with higher pain levels and more active disease. Disclosure: K. Quinn: None. G. Murphy: None. L. Larkin: None. H. O' Leary: None.